пожалуйста упростите выражение 1)5(3-5a)^2-5(3a-7)(3a+7)= 2)(m-1)^2-4(m+1)^2-6(m+1)(m-1)= 3)5(1-y)^2-(3+y)^2-3(1-y)(1+y)= 4) 5(1+M)(1-M)-(2-M)^2-8(1-M)^2= решите пожалуйста

1

Ответы и объяснения

2012-12-08T16:15:07+04:00

1)5(3-5а)2-5(3а-7)(3а+7)=30-50а-5(9а(в квадрате)-49)=30-50а-45а(в квадрате)-245=50а- 45а(в квадрате)-215=5(10а-9а(в квадрате)-43).

2)(m-1)^2-4(m+1)^2-6(m+1)(m-1)=2m-2-8m-8-6(m(в квадрате)-1)=-6m-10-6m(в квадрате)+6= 6m-4-6m(в квадрате)=2(3m-2-3m(в квадрате).

3)5(1-y)^2-(3+y)^2-3(1-y)(1+y)=10-10у-6-2у-3+3у(в квадрате)=1-12у+ 3у(в квадрате). 

 

 4)5(1+M)(1-M)-(2-M)^2-8(1-M)^2= 5-5М(в квадрате)-4+2М-16+16М=-15-5М(в квадрате)+18M.